A new dynamic visualization technique for system dynamics simulations (2014)
This article addresses a main research question in System Dynamics, the correct understanding of the relationship between model structure and behavior, from a new perspective: the field of Information Visualization. We propose a new dynamic visualization technique that is different from the current static visualization techniques. The technique was applied to a classical case and tested through visual and interactive software built as proof of concept. The case illustrated the potential of the new technique to confront the problem by providing the user a visual experience in real time, so his/her understanding could be more direct and immediate. This visualization technique could be adapted and generalized to other simulation methodologies.